L’Exposition Universelle de 1900 et le voyage Barcelone - Paris - Mireia Freixa (Catalonia)
The Paris 1900 Universal Exhibition is particularly important for its contribution to the spread of Art Nouveau, a style that nevertheless collects more in the streets than in the official pavilions of the exhibition, still built in an eclectic style. The Spanish pavilion, constructed by José Urioste becomes the reference of the new regionalist architecture in Spain but this event has had a relative influence on art and architecture in Catalonia. There the modernity had already committed a decade ago, towards what we call « first modernity », since 1888 Barcelona World Exhibition. But the Paris one exerts enormous power of attraction on artists and Catalan intellectuals and sensitizes Catalan culture with a cosmopolitan spirit and becomes mainly a city model – as a modern European metropolis - for Barcelona citizens. This research was made from materials that attest to the event's success: catalogues, postcards, tourist brochures, letters and personal documents in archives and with the weekly magazine Pèl & Ploma.